A cognitive-creative profile of emotional talent - Rosario Bermejo; María Dolores Prieto; Mari Carmen Fernández; Gloria Soto; Marta Sainz (Springer, 2013)
Much attention has been paid to emotional intelligence and its correlations with other psychological constructs during the last few years. Nevertheless, studies focusing on emotionally intelligent persons are scarce. The present work aims to study the cognitive and creative profile of students who stand out for their high emotional intelligence. A total of 1,024 Secondary Education students (M= 14 years old, SD= 1.16) took part in our research to that end. Emotional Intelligence was measured using the Emotional Quotient inventory Youth Version (EQ-i:YV, Bar-on & Parker, 2000), the Differential Aptitude Test-5 (DAT-5, Bennett, Seashore, & Wesman, 2000) was used to measure intellectual competency, whereas the Torrance Test of Creative Thinking (TTCT, Torrance, 1974) served to measure creativity.  Participants were divided into two groups: those with a high emotional intelligence (pc > 75) and those with a low-average emotional intelligence (pc < 75). The results reveal statistically significant differences in numerical reasoning, spatial reasoning and perceptive speed favouring the low-average emotional intelligence group. No statistically significant differences were found for creativity dimensions depending on the emotional intelligence level.